X-Shaped Slotted Patch Biomedical Implantable Antenna for Wireless Communication Networks. (17th January 2022) - Ahmad, Sarosh; Manzoor, Bilal; Naseer, Salman; Santos-Valdivia, Nilton; Ghaffar, Adnan; Abbasi, Muhammad Inam
Abstract : Biomedical implantable antennas have a major role in biomedical telemetry applications. Therefore, a compact-size low-profile implantable antenna working in industrial, scientific, and medical (ISM) band at 915 MHz is presented. The presented antenna is a simple slotted patch fed with a coaxial probe of 50  Ω impedance. The patch consists of four slotted resonators printed on a flexible Roger Duroid RT5880 substrate (ε r = 2.2, tan δ = 0.0009 ) with the standard thickness of 0.254 mm. The complete volume of the designed antenna is 7   mm × 7   mm × 0.254   mm (0.08 λ g × 0.08 λ g × 0.003 λ g ). The antenna covers the bandwidth from 800 MHz to 1 GHz (200 MHz) inside skin tissue. A good agreement between the simulation and measurements of the antenna has been obtained. Finally, the specific absorption rate (SAR) values have also been analyzed through simulations as 8.17 W/kg inside skin over 1 g of mass tissue. The proposed SAR values are less than the limit of the Federal Communications Commission (FCC). This antenna is miniaturized and an ideal applicant for applications in biomedical implants.